OPTIMALISASI PERAN MEDIA SOSIAL GUNA MENINGKATKAN KESADARAN BELA NEGARA - Murtopo, Adi; Martono, Agus Djoko; Budiyanto (JURNAL DWIJA KUSUMA, 2024)
The rapid development of social media has changed the face of the world and shifted the understanding of a country's strength to no longer being judged solely on military or economic strength, but also depending on mastery of the role of social media. The influence of social media on the character of society today can be used to foster a sense of love for the country so as to increase awareness of defending the country. Using the descriptive analysis method, it explains that social media can be used as a very effective disseminator of information to change a person's attitude if it fulfills five elements, namely communicator, message, media, communicater, and effect. Accurate, timely, relevant and complete information through communication planning on social media using The Circular Model of SOME can have a significant effect on changing the character of society in terms of awareness of defending the country. Understanding the rules and digital literacy can prevent misuse of social media. Software regarding the role of social media in increasing national defense is very necessary to regulate the boundaries of authority so that cooperation between the TNI and Regional Government can be carried out well. Integration between Satkowil and other related agencies is needed to successfully implement the role of social media in increasing awareness of defending the country. The development of national defense awareness is carried out according to procedures starting from the planning, preparation, implementation and closing stages by utilizing the role of social media which can be used to foster the character of love for the homeland, national and state awareness and national insight.